Europe in Identity Crisis : The Future of the EU in the Age of Nationalism - Altomontee, Carlo; Villafranca, Antonio; Altomontee, Carlo; Villafranca, Antonio (2020)
Today$1 (Bs European Union is in an identity crisis as it seems to be losing its points of reference. The principles that upheld its creation are being increasingly questioned around the world and within the EU itself. Its chances to survive hinge upon its ability to deliver at home and abroad, without abandoning its values and principles but rather adapting and re-launching them. This volume offers policy options on key questions for the future of the EU: How to scale-up its role abroad? How to benefit from new partners without severing ties with traditional allies such as the US? How to contain Eurosceptic forces by reducing inequalities? And how to reinforce the euro while aiming at more sustainable and balanced growth?s
Knowledge Unlatched
English
Keywords: International relations; Political Science; International Relations